Dynamic modelling of pectin extraction describing yield and functional characteristics. (January 2017) - Andersen, N.M.; Cognet, T.; Santacoloma, P.A.; Larsen, J.; Armagan, I.; Larsen, F.H.; Gernaey, K.V.; Abildskov, J.; Huusom, J.K.
Abstract: A dynamic model of pectin extraction is proposed that describes pectin yield, degree of esterification and intrinsic viscosity. The dynamic model is one dimensional in the peel geometry and includes mass transport of pectin by diffusion and reaction kinetics of hydrolysis, degradation and de-esterification. The model takes into account the effects of the process conditions such as temperature and acid concentration on extraction kinetics. It is shown that the model describes pectin bulk solution concentration, degree of esterification and intrinsic viscosity in pilot scale extractions from lime peel at different temperatures (60 °C, 70 °C, 80 °C) and pH (1.5, 2.3, 3.1) values. Highlights: A dynamic model for pectin extractions is presented describing yield and functional quality attributes. A strategy for experiments and parameter estimation is proposed in relation to the developed model. Successful fitting to pilot scale data using a composite design of experiment.